2009
DOI: 10.1063/1.3151865
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of electrical instabilities in top-gate InGaZnO thin film transistors with Al2O3 and Al2O3/SiNx gate dielectrics

Abstract: A comparative study was made of the performance and electrical instabilities in amorphous indium-gallium-zinc oxide (a-IGZO) thin film transistors with Al2O3 and Al2O3/SiNx gate dielectrics. Steeper subthreshold slope is observed in Al2O3 devices, which shows that the density of trap states at the interface of a-IGZO/Al2O3 is lower than that of a-IGZO/SiNx. Under high bias-stresses, a larger degradation is observed in Al2O3/SiNx devices. The device degradation for both devices are mainly attributed to the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…The electrical stabilities of amorphous indium gallium zinc oxide (a‐IGZO) thin film transistors (TFTs) have been astonishingly improved, allowing them to be applied in large size Organic Light Emitting Diode (OLED) TV products and high resolution Liquid Crystal Display (LCD) monitors . The stability under positive bias temperature stress (PBTS) of a‐IGZO TFT, which is the main requirement for a TFT for OLED driving, was achieved by minimizing charge trapping sites in the front and back interfaces, and active layer . Hydrogens (H) in the active layer, gate insulator (GI), passivation layer, and substrate buffer layer are key passivators of these defects .…”
Section: Introductionmentioning
confidence: 99%
“…The electrical stabilities of amorphous indium gallium zinc oxide (a‐IGZO) thin film transistors (TFTs) have been astonishingly improved, allowing them to be applied in large size Organic Light Emitting Diode (OLED) TV products and high resolution Liquid Crystal Display (LCD) monitors . The stability under positive bias temperature stress (PBTS) of a‐IGZO TFT, which is the main requirement for a TFT for OLED driving, was achieved by minimizing charge trapping sites in the front and back interfaces, and active layer . Hydrogens (H) in the active layer, gate insulator (GI), passivation layer, and substrate buffer layer are key passivators of these defects .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a band alignment diagram is a guide to choose appropriate constituent materials because it helps to predict the electronic structures and performances of the heterojunction devices such as band bending, electron transport in the interface, and built-in potential [12]. By far, many gate dielectrics, such as Al 2 O 3 , ZrO 2 , and SiN x , have been investigated to fabricate IGZO-based TFTs [13][14][15]. However, the smaller band offsets at the high-k/IGZO interface and smaller dielectric constant lead to the inferior negative bias and the increased leakage current, which prevents the successful integration of these gate dielectrics into IGZO-based TFTs [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, top-gate structure TFTs have attracted lots of attention with the merits of being self-passivated and compatible with the AMOLED process [7,8]. Jeong et al have reported top-gate InGaZnO thin film transistors with Al 2 O 3 and Al 2 O 3 /SiN X gate dielectrics and found larger degradation in devices with a SiN X interfacial layer due to the trapped charge located at energetically shallower states [9]. Lin et al have reported top-gate staggered IGZO TFTs by adopting the SiO X /SiN X bilayer gate-insulator stack, and finally integrated the devices into a working OLED panel [10].…”
Section: Introductionmentioning
confidence: 99%